Desenvolvimento de coração bioartificial a partir de arcabouço de matriz extracelular descelularizada enriquecida com fibronectina plasmática humana - Taufner, Gabriel Henrique (2023)
The reconstruction of complex organs after decellularization presents as the greatest challenge the delivery, adhesion, proliferation and differentiation of cells. To succeed in the process, it is necessary to mimic the in vivo microenvironment as much as possible. It is known that decellularization is capable of removing important biomolecules in the morphophysiology of the organ, such as glycosaminoglycans and glycoproteins such as fibronectin. Fibronectin remaining in the extracellular matrix after the decellularization process may not be sufficient to satisfactorily promote the tissue reconstruction process, especially if the scaffold is in the adult stage of development, where the composition of said glycoprotein is known to be reduced. In our study, we obtained decellularized scaffolds to investigate the influence of human plasma fibronectin on adult mouse heart reconstruction. We demonstrated that the decellularized scaffolds were considerably preserved in terms of their matrisomal biomolecular composition. We emphasize the maintenance of the hydroxyproline molecule, found in a concentration of 5,509 ± 818.13 vs. 4,881 ± 1,487 µg/total dry weight in decellularized adult organ and control respectively. Regarding neonatal decellularized scaffolds, we observed maintenance of hydroxyproline when compared to its native control (330.5 ± 17.60 vs. 273.9 ± 12.30 µg/total dry weight). In addition to matrisomal biomolecules, we emphasize the remarkable reduction of DNA (83.63% and 93% in neonatal and adult respectively) and residual SDS (33.92% and 96.44% in neonatal and adult respectively), interfering with the reconstruction process . We investigated the use of a non-destructive analytical approach for decellularized tissues: Raman spectroscopy, whose results corroborated the spectrophotometric analyzes of matrisomal biomolecules. We established an effective strategy for the recomposition of fibronectin in adult decellularized scaffolds, however, we found that despite the success in the recomposition of the glycoprotein, we did not find statistical significance after the reconstruction of the organs from cells of the H9c2 lineage. Given this last finding, we suggest additional studies capable of investigating other classes of fibronectin. Furthermore, it is also necessary to investigate cell populations beyond the H9c2 lineage.